Nasolacrimal Duct Neoplasm in a Bitch - Moro Bassil Dower, Nathalie; Ghisi Gomes, Lianna; Ribeiro Fiori, Marina; Viccini Galli, Fernanda; da Costa Junior, Augusto Roberto; Paulino de Figueiredo Wouk, Antônio Felipe (Acta Scientiae Veterinariae, 2022)
Background: Nasolacrimal duct tumors are divided into primary and secondary, with primary tumors being rare in all species. Secondary involvement of the lacrimal sac and duct can occur from any skin lesion involving the eyelid and/or conjunctiva and from any neoplastic process involving the paranasal sinuses. Lacrimal sac metastatic lesions may originate from any distant site and include carcinomas or melanomas, with squamous cell carcinoma being the most common type. The objectives of the present report were to describe a case of squamous cell carcinoma in the nasolacrimal duct and to emphasize the importance of a good ophthalmic evaluation. Case: A 16-year-old spayed bitch white poodle was presented to the veterinary clinic. The owner complained that the animal had epiphora and mucoid secretion in the right eye, eyelid hyperemia in both eyes, and sporadic sneezing with blood. On ophthalmic examination, the animal was initially diagnosed with nasolacrimal duct obstruction and right eye (OD) blepharitis and OU uveitis. Fourteen days after the first evaluation, the nasolacrimal duct region increased, with the presence of bloody secretion. Biomicroscopy showed nodules inside the lacrimal duct, in the punctum region. The animal was sedated to obtain a fragment of the nodule for histopathological analysis, and a subsequent oral cavity evaluation identified a nodule in the transition region between the 4th premolar and 1st molar, which was sent for cytology. Cytology of the medial corner region of the RE showed epithelial and mesenchymal cells with malignancy characteristics, and the biopsy was suggestive of malignant epithelial neoplasia (carcinoma). A surgical procedure for nodule resection was ruled out because bone involvement was extensive, and chemotherapy was selected. The patient died 2 months after the 1st consultation. The diagnosis was confirmed through necropsy via immunohistochemical tests, demonstrating squamous cell carcinoma (SCC) both in the mouth and the nasal and ocular sinuses. Discussion: The most common conditions affecting the nasolacrimal drainage system in dogs are those causing obstructions. These may be congenital, arising from a developmental defect of micropunctum or agenesis of the punctum, they may be acquired, arising from infection and inflammation. SCC is a malignant neoplasm originating in the stratified squamous epithelium. The predisposing factors in cats and dogs include lack of adnexal pigmentation and, possibly, chronic irritation of the ocular surface. A light coat is considered a relevant factor, especially in regions with little hair coverage. In addition to a mass lesion, other clinical signs of eyelid or ocular surface tumors may include epiphora, conjunctival vascular injection, mucopurulent ocular discharge, 3rd eyelid protrusion, conjunctival/corneal roughness or ulceration, and corneal neovascularization or pigmentation. Clinical presentations are nonspecific. Neoplasms, whether nasal and/or in the maxillary sinus, can invade the nasolacrimal duct and spread to the nasal cavity, and neoplasms in the nasal cavity can invade the nasolacrimal duct. Ophthalmic evaluation along with good inspection of the oral cavity is a useful tool in the diagnosis of eye neoplasms that may have effects on the oral cavity or vice versa due to the strong association between them. Early diagnosis is crucial for the clinical or surgical management of each case of ophthalmic neoplasia and for therapeutic success. Keywords: neoplasm, tumor, nasolacrimal duct, dog, eye. Título: Neoplasia de ducto nasolacrimal em uma cadela Descritores: neoplasia, tumor, canalículo lacrimal cão, olho.